Small gas engine repair - Dempsey, Paul (McGraw-Hill, 2008)
The Third Edition of Small Gas Engine Repair shows you how to troubleshoot and repair virtually any type of small gas engine used in garden equipment, chain saws, pumps, and standby generators. Completely revised and updated and offering a step-by-step approach, this bestseller covers all you need to know to repair and maintain a small gas engine and get professional results while saving money. This in-depth guide by master mechanic Paul Dempsey includes the latest in small engine technology and gives you up-to-date information on overhead valve and overhead cam engines, carburetion advances, digital ignition systems, and more. Dempsey explains how to troubleshoot and repair both two- and four-cycle engines. The author also reveals the shortcuts, field fixes, and other tricks of the trade that only working mechanics know. -- from publisher's description.